The Management Of Innovation Initiation In Islamic Education And Its Implications For Madrasah Competitiveness: A Multisite Qualitative Study - Hawwin Muzakki; Ngainun Na’im; Mujamil Qomar (International Journal of Education Management and Religion, 2026)
This study examines the management of innovation initiation in Islamic education and its implications for strengthening madrasah competitiveness, using MAN 2 Tulungagung and MAN 2 Kota Kediri as multisite cases. While existing studies on Islamic educational innovation primarily focus on implementation and outcomes, the initiation phase of innovation remains underexplored, particularly in the context of madrasah management. Employing a qualitative phenomenological approach within a naturalistic paradigm, this research explores how innovation initiation is strategically managed across three domains: curriculum, student development, and human resources (teachers). The findings indicate that innovation initiation is driven by benchmarking, internal awareness building, and systematic identification of student potential through psychological and talent–interest assessments. MAN 2 Tulungagung initiated innovation through talent-based superior classes and differentiated instruction aligned with the Merdeka Curriculum, supported by structured teacher development. In contrast, MAN 2 Kota Kediri adopted an integrative model that connects intrakurikuler, kokurikuler, and ekstrakurikuler programs through its “Red Carpet” philosophy, emphasizing holistic talent development and character formation. Across both sites, innovation initiation is characterized by collaborative decision-making, curriculum flexibility, professional learning communities, and strong leadership commitment. This study contributes novel insights by conceptualizing innovation initiation as a strategic managerial process that precedes implementation and directly shapes institutional competitiveness. It demonstrates that innovation initiation grounded in Islamic educational values functions as a foundational driver of academic excellence, institutional differentiation, and sustainable competitive advantage in contemporary madrasahs.